Território, cultura e comunidade: O Centro de Memória da Cultura Negra Graça do Aché em Uberlândia - Dutra, Mariana Cortes (2024)
This master's thesis aims to investigate the role of the Centro de Memória da Cultura Negra Graça do Aché in Uberlândia-MG and its appropriation by the city's black community. This center, also known as Graça do Aché or Graça, is a cultural facility of the Universidade Federal de Uberlândia and its mission is to promote and disseminate the culture and customs of the Afro-Brazilian community; the name is a tribute to Maria da Graça de Oliveira, an activist of the black movement in the city who founded Bloco Aché in 1988, one of the most representative carnival blocks of the black community in the city. In order to understand the work of this space and investigate its appropriation by the community, we have drawn mainly on the discussions of social museology, addressed by Mário Chagas, the notion of territory for Milton Santos and culture, for Chauí. The methodological approach consists of a bibliographical survey, a documentary survey and interviews with people linked to the management of Graça, which form the corpus of the research. In this investigation, it was possible to observe the presence of two black women who, as coordinators of Graça, contributed to bringing the community closer to Graça, which points to the importance of thinking about representative coordinators in the management of cultural facilities.